Antibiotic prescribing patterns for patients with pharyngitis in Malaysian public primary care clinics - Muthanna, AbdulRahman; Zakariah, Siti Zulaikha; Abdul Rashid, Aneesa; Shariff Ghazali, Sazlina; Awang Hamat, Rukman; Mawardi, Maliza; Salim, Hani Syahida; Shamsuddin, Nurainul Hana (Penerbit Universiti Sains Malaysia, 2022)
Background: Over-prescription of antibiotics for upper respiratory tract infection (URTI) is a continuing problem in Malaysia, leading to increased antimicrobial resistance and unnecessary cost incurred for treatment. In a patient presenting with a sore throat, it is recommended to only prescribe antibiotics to group A streptococcus (GAS) pharyngitis confirmed by a throat culture, rapid antigen test or in patients with a Centor score of 4. Methods: This cross-sectional study assessed the proportion of antibiotics prescribed and antimicrobial susceptibility patterns of GAS pharyngitis in the Malaysian primary care setting. Two-hundred and fifteen adult patients presenting with sore throat were recruited in three primary care clinics. Demographic data and clinical information were collected and analysed. Centor scores were calculated according to the clinical information and throat swabs were collected from all participants for GAS identification. Results: Only six throat swabs isolated GAS and indicated for antimicrobial treatment (2.8%). However, 48 participants (22.3%) were prescribed antibiotics out of which only four (8.3%) patients with isolated GAS, including three (6.2%) patients who clinically had a Centor score of 4 and one patient with a score of 3. Amoxicillin and erythromycin were the most commonly prescribed antibiotics (58.3% and 25% of all antibiotics, respectively). Conclusion: There is a high proportion of antibiotic prescriptions which were not indicated in patients with sore throat in this study. This may reflect a common practice of antibiotic overuse for sore throat in primary care settings in Malaysia. Concerted interventions to reduce the inappropriate prescribing of antibiotics are urgently needed.